Tractor-implement performance mapping system. - Yahya, Azmi; Bardaie, Mohd. Zohadie; Kheiralla, Abdelmotalab Fadlelmola; Gew, Soon Kiat (2004)

(untitled)
Management decision related to agricultural machinery can affect plantation profits in many ways. Fuel, interest, labour and timelines are the pertinent factors that contribute to a tractor`s productivity and efficiency. To improve productivity and efficiency, it is necessary to have comprehensive information on all aspects of the tractor and implement performances in the plantations. The system can measure, display and record in real-time tractor`s theoretical travel speed, actual travel speed, pitch and roll angles fuel consumption rate, drive wheel slippage, drive wheel torque and implement`s PTO torque, plowing depth, drawbar force, and three-point hitch forces. With the added DGPS option, the system can be used for spatial mapping implement field performances. Under such configuration, the system can measure, display of the tractor-and record in real time tractor-implement`s geo-position in the field with respect to its measured performances.